Phenotypic characterization of Creole cattle in the Huascaran National Park – Ancash, Peru - Delgado C., Alfredo (2019)
The aim of this study was to evaluate the phenotypic characteristics of the Creole cattle of the Huascarán National Park (PNH), Ancash, Peru through zoometric measurements and indexes of productive interest. The study was conducted in a population of Creole cattle in the Llanganuco zone of the PNH. Data were collected from 32 cows bovines. The zoometric measurements were head width (AC), head length (LC), chest girth (PT), body length (LCU), height withers (ALC) and height at the rump (ALG), anterior rump width (AAG), rear rump with (APG) and rump length (LG). Indexes related to meat ability were calculated: transversal pelvic index (IPT) and longitudinal pelvic index (IPL), and ethnological indexes: anamorphosis index (AI), corporal index (IC), pelvic index (PI) and proportionality index (IPR). The data were processed with the statistical program R. The colour and pattern of the coat were registered applying the nomenclature for Spanish bullfighting cattle. The zoomometric measurements showed a low CV (4.29 – 9.25), except for APG (14.75), reflecting morphological uniformity in the sample. The zoometric indices showed CV less than 10% (5.89 – 7.11), except for the AI ​​(16.28) and IC (11.5). As for the coat, a tendency towards simple colours (46.9%) with a predominance of black was observed. In general, the Creole bovine of the Quebrada de Llanganuco presents similar indexes with the Creole bovine from Ayacucho, Peru, classifying it as a short-bodied animal.